Case Study/Toyota Financial Services-Creating a Foundation for Leadership Development - Berke, David; Fike, Judy (Center for Creative Leadership, 2007)
How can organizations establish a leadership strategy and implementation process that goes well beyond the typical approach of using training as the primary or only methodology? The short answer is that they need to develop a talent mind-set --an orientation in which the organization's talent (its people) is recognized as a significant part of the organization's competitive advantage.
Online resource; Title from title page (viewed January 1, 2007)
Keywords: Electronic books; local